Evaluasi Pertumbuhan Tanaman Meranti (Shorea spp.) di Haurbentes BKPH Jasinga KPH Bogor Perum Perhutani Unit III Jawa Barat - I Istomo; Cahyo Wibowo; Nurul Hidayati (Jurnal Manajemen Hutan Tropika, 1999)
Planting trials of Shorea spp. have been conducted outside their natural distributional range. Initially it was planted in Haurbentes Experimental Garden (1940) at Jasinga, West Java. This research is intended to get information about growth of all of Shorea's variety that have been planted at 1984, 1988 and 1992 at the location, so we can select the species that suitable to be explored. From each of them, we take four sample plots. The size of the sample plot is 50 m x 50 m or about 0,25 ha. The results of the trial showed that Shorea spp. stand was flowering and giving a good seed harvest.  It was also shown that the biggest growth species is Shorea leprosula Miq., namely 30,65 cm (total height) and 19,88 m (diameter) at 13 years old. The averages of the height and diameter growth are 0,49-0,66 m and 0,48-0,64 cm per 6 month at 9 years old. The species that are suggested to be explored at the location are S. leprosula Miq., S. stenoptera Burck, S. stenoptera Burck forma and S. pinanga Scheff.